2012
DOI: 10.1002/ejic.201101178
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Spin Crossover and Coordination Core Distortion in a Family of Binuclear Iron(II) Complexes with Bipyridyl‐Like Bridging Ligands

Abstract: The synthesis and characterization of two new binuclear compounds [{Fe(dpia)(NCS) 2 } 2 (bpac)]·nCH 3 OH [n = 0 (1) and 2 (2), dpia = bis(2-picolyl)amine, bpac = 1,2-bis(4-pyridyl)ethyne] are reported. The magnetic susceptibility measurements of the compounds revealed different types of magnetic behavior. Complex 1 displays a two-step spin crossover (SCO) that suggests the occurrence of a mixed [HS-LS] (HS = high spin, LS = low spin) pair at the plateau temperature (145 K), at which about 50 % of the complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 61 publications
2
41
0
Order By: Relevance
“…As Figure 4a exemplifies, the CShM vs. σ p plot has a relation with a negative slope, implying that the electron-donating group would favor a distorted structure. Such distortion would bring about preference for the HS states due to reduction of the ligand-field strength [42][43][44][45] and suppress the SCO temperature. Gao and co-workers have already reported the SCO study on a [Fe(H-pybox) 2 ] 2+ series with counter anion and solvent variation [25] with the substituent X fixed to H, and the magneto-structural relation was clarified to give a partially similar conclusion: highly distorted structures are favorable for the HS state and only intermediately distorted compounds show SCO.…”
Section: Coordination Structure Effectmentioning
confidence: 99%
“…As Figure 4a exemplifies, the CShM vs. σ p plot has a relation with a negative slope, implying that the electron-donating group would favor a distorted structure. Such distortion would bring about preference for the HS states due to reduction of the ligand-field strength [42][43][44][45] and suppress the SCO temperature. Gao and co-workers have already reported the SCO study on a [Fe(H-pybox) 2 ] 2+ series with counter anion and solvent variation [25] with the substituent X fixed to H, and the magneto-structural relation was clarified to give a partially similar conclusion: highly distorted structures are favorable for the HS state and only intermediately distorted compounds show SCO.…”
Section: Coordination Structure Effectmentioning
confidence: 99%
“…Temperature-dependent magnetic measurements of the 1D isomer [Fe(NCS) 2 (4-Acpy) 2 ] n at 200 Oe reveal antiferromagnetic ordering at T N = 4.5 K. Field-dependent measurements show a metamagnetic transition into a saturated paramagnetic phase at a critical field of ca. 700 Oe.…”
Section: Introductionmentioning
confidence: 96%
“…Coordination polymers based on metal cations with unpaired electrons are of increasing interest, because of their different magnetic properties, such as spin-crossover or low-dimensional magnetism. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] In several cases, the metal cations are linked by small, two-or three-atom ligands (e.g., cyanide or azide anions) into coordination networks of different dimensionality, and some examples are given in refs. [17][18][19][20][21][22][23][24][25][26][27][28][29] In this regard, thiocyanato anions are also of interest because of their ambidentate nature and versatile coordination modes.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] It has been shown that serious differences in the degree of distortion of FeN 6 chromophore geometries can lead to various spin-crossover behaviors: One-step, twostep, or incomplete (50 %) transitions. On the other hand, our investigations of 3D network [Fe(qbtr) 3 ](ClO 4 ) 2 containing flexible ligand bridges did not reveal any influence of conformational alterations on the FeN 6 geometry.…”
Section: Resultsmentioning
confidence: 99%
“…[19] It is also assumed that in dinuclear complexes containing crystallographically unique iron(II) ions, intermolecular interactions influence spin-crossover properties leading to the occurrence of an intermediate phase comprising LS-HS or 50 % HS-HS and 50 % LS-LS pairs. [24] Investigations of dinuclear complexes based on 1,2-bis(4-pyridyl)ethane, [25] bis(2-picolyl)amine, [26] and 1,2-bis(4-pyridyl)ethyne [27] showed that a degree of distortion in the [FeN 6 ] chromo-phore caused by ligand strain and packing effects is responsible for spin-crossover (SCO) behavior. It is worth noting that the number of steps in the spin-transition curve does not necessarily match the number of crystallographically distinct iron(II) ions in a crystal lattice.…”
Section: Introductionmentioning
confidence: 99%